Zooarchaeology of a Focal Resource : Dietary Importance of Beluga Whales to the Precontact Mackenzie Inuit - Friesen, T. Max; Arnold, Charles D. (ARCTIC, 1995)
Ethnohistoric records indicate that the economy of early historic Mackenzie Inuit was centred on the summer hunt for beluga whales (Delphinapterus leucas). However, no systematic attempt has been made to quantify the dietary importance of beluga whales to earlier, precontact-period Mackenzie Inuit societies. This issue is addressed herein through analysis of over 2000 beluga bones recovered from a semisubterranean house at Gupuk, a Mackenzie Inuit archaeological site on the East Channel of the Mackenzie River. The amount of meat and fat available from beluga whales is compared to that from all other prey species at the site to assess the relative dietary contribution of each taxon. The results indicate that beluga whales were a truly focal resource in the local economy, probably providing over half of the food available to residents of Gupuk and other communities in the Mackenzie Delta for at least half of each year.Key words: beluga whale, white whale, Delphinapterus leucas, Gupuk, Kittigazuit, Mackenzie Inuit, Inuvialuit, Mackenzie Delta, zooarchaeology, archaeology Les relevés ethnohistoriques indiquent que l'économie des Inuit du Mackenzie du début de l'époque historique était centrée sur la chasse estivale au bélouga (Delphinapterus leucas). Aucun essai systématique n'a cependant été réalisé dans le but de quantifier l'importance alimentaire du bélouga pour les anciennes sociétés inuits du Mackenzie d'avant le contact avec les Européens. Grâce à l'analyse de plus de 2000 os de bélougas récupérés dans une habitation semi-souterraine de Gupuk, site archéologique inuit du Mackenzie sur le chenal est de la rivière Mackenzie, on a pu comparer la quantité de viande et de gras venant du bélouga à celle de toutes les autres espèces de proies sur le site afin d'évaluer la contribution alimentaire relative de chaque taxon. Les résultats indiquent que le bélouga était véritablement une ressource primordiale dans l'économie locale, fournissant probablement plus de la moitié de la nourriture disponible aux résidents ...